Efficacy of photodynamic therapy in the treatment of Pseudomembranous oral candidiasis - سليمان, حسين; عمار مشلح ,; عبير الكفري, (Latakia University Journal -Medical Sciences Series, 2022)
Background: Photodynamic therapy (PDT) using methylene blue (MB) has been shown to be an effective method for the in vitro and in vivo inactivation of Candida species, however, there are limited reports of clinical investigations. The aim of this study was to explore the clinical application of PDT with MB for the treatment of oral infection caused by C. albicans in patients undergoing chemotherapy. Methods: A total of 10 adult patients with pseudomembranous oral candidiasis (8 males, 2 females) received six sessions PDT treatments with methylene blue (450µg/mL) for 2 weeks. Immediately before and after the treatments, C. albicans yeast isolates were recovered to measure the colony-forming units (CFUs ) , and after (15,30,60 days). Patients were assessed for the clinical recovery of oral lesions and improvement of symptoms, and the microbiological evaluation was determined by microbiological collections from the mucosa of the infected area and were seeded and on Sabouraud agar. Results: this study demonstrates that PDT with MB decreased the CFUs immediately after treatment and decreased the oral lesions and clinical symptoms . There was a relapse at 15,30 and 60 days for clinical and microbiological evaluation. Conclusions: This clinical study suggests that PDT with MB could reduce the fungal load and improve the clinical symptoms of oral candidiasis in patients undergoing chemotherapy after treatments but still presented observed relapse in clinical and microbiological response after 15,30,60 days